2017
DOI: 10.1021/jacs.6b11273
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Inhibition of microRNA-210 Reprograms an Oncogenic Hypoxic Circuit

Abstract: A hypoxic state is critical to the metastatic and invasive characteristics of cancer. Numerous pathways play critical roles in cancer maintenance, many of which include noncoding RNAs such as microRNA (miR)-210 that regulates hypoxia inducible factors (HIFs). Herein, we describe the identification of a small molecule named Targapremir-210 that binds to the Dicer site of the miR-210 hairpin precursor. This interaction inhibits production of the mature miRNA, derepresses glycerol-3-phosphate dehydrogenase 1-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
169
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 146 publications
(170 citation statements)
references
References 37 publications
1
169
0
Order By: Relevance
“…The above results confirm that PDC17‐H effectively delivered anti‐miR‐210 to MDA‐MB‐231 cells and downregulated cellular miR‐210 levels. Previous reports showed that downregulation of miR‐210 inhibits proliferation and induces apoptosis in cancer cells . We thus hypothesized that PDC17‐H/anti‐miR‐210 polyplexes will show improved cell killing activity in cancer cells.…”
Section: Resultsmentioning
confidence: 93%
“…The above results confirm that PDC17‐H effectively delivered anti‐miR‐210 to MDA‐MB‐231 cells and downregulated cellular miR‐210 levels. Previous reports showed that downregulation of miR‐210 inhibits proliferation and induces apoptosis in cancer cells . We thus hypothesized that PDC17‐H/anti‐miR‐210 polyplexes will show improved cell killing activity in cancer cells.…”
Section: Resultsmentioning
confidence: 93%
“…The results of this study may be applied to future studies to identify new therapeutic targets against tau-associated diseases. 32,[79][80][81][82] 1: Schematic representation of cell-based assays with mini-genes expressing wild type tau or tau with mutations in intron 9 or 10. 30,32 Mini-genes contain exon 10 in frame with a firefly luciferase reporter gene.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, our method sheds light on evaluation of post-transcriptional impact of genetic mutations especially for synonymous mutations. Additionally, as small molecules can be rapidly designed to selectively target RNAs and affect RNA-RBP interactions 54 , our study provides new insights into RNA-based therapeutic strategies for the treatment of neuropsychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%